The Relationship of Spiritual Health with the Quality of Life of Cancer Patients - Warsini, Warsini; Yulianti, Tunjung Sri; Kristanto, Budi; Qomariah, Siti Nur; Orizani, Chindy Maria; Iswati, Iswati (STIKES Adi Husada, 2024)
The number of cancer patients is increasing from year to year, the low cure rate of cancer patients increasingly shows many influencing factors. For patients diagnosed with cancer, initial health conditions will decline. In this situation, it is necessary to fulfill the spiritual health needs of cancer patients to reduce the negative impact on the patient's quality of life. To deal with cancer disease management such as: chemotherapy, surgery, radiotherapy requires a good quality of life so as not to slow down the healing process. The purpose of this study was to explain the relationship between the fulfillment of basic spiritual health needs and the quality of life of cancer patients. This type of research is an observational analytic with a crosssectional design to determine the relationship between fulfilling basic spiritual health needs and the quality of life of cancer patients. The study population was cancer patients at the Indonesian Cancer Foundation, Cancer Patient Shelter and Patients at Dr. Moewardi Surakarta Hospital. The study sample size was 100 respondents who were taken using non-probability sampling technique type purposive sampling. The instrument used was a questionnaire and data analysis using the Pearson Chi Square test. The results showed that the majority of respondents' gender was female (65%), the majority of respondents' last education was elementary school or equivalent (49%), the majority of respondents' spiritual health was in the moderate category (68%) and the majority of respondents' quality of life was in the good category (69%). The results of the Pearson Chi Square test analysis showed that there was a statistically significant relationship between the fulfillment of basic human needs for spiritual health and the quality of life of cancer patients (p=0.018). The entire health team caring for patients with cancer should be able to fulfill the spiritual needs of patients as much as possible by involving support from the family.